Effects of Torbangun Leaves(Coleus amboinicus Lour) Extract on Blood Glucose and Super Oxide Dismutase Activity in Hyperglycemic Rats - Andrestian, Meilla Dwi; Damanik, Muhammad Rizal Martua; Anwar, Faisal; Yuliana, Nancy Dewi (Jurnal Gizi dan Pangan, 2019)
This research aimed to analyze the yield of torbangun extract, flavonoid content, and antioxidant activity of TE-S and its effect on the activity of SOD enzymes and blood glucose level in hyperglycemic rats as a DM animal model. The water content of simplicia was measured by the gravimetric method. The antioxidant activity of TE-S was determined using the DPPH method, while the total flavonoid was measured using spectrophotometry. The study was a completely randomized design using 25 Sprague Dawley rats. Rats were divided into four groups, namely NG (negative control, hyperglycemic rats), N (normal rats), H-IM (control of metformin drugs 62.5 mg/kg of BW), and H-IT (TE-S 620 mg/kg of BW). The treatment was carried out for 14 days. FBG levels were taken on day 0, 4, 7, 11, and 14, measured using a glucometer, while blood serum SOD levels were measured using ELISA. The study showed the water content of torbangun simplicia was 7.99% and TE-S yield from simplicia was 4.69%. TE-S contains total flavonoids of 3.91% and antioxidant activity (IC50) of 306.28 ppm with a standard of 1 ppm vitamin C. TE-S treatment significantly decreased FBG (p=0.005, α=0.01) and increased SOD levels in hyperglycemic rats. TE-S has the potential to increase blood serum SOD levels by contributing to the availability of antioxidants and decreasing blood glucose levels in hyperglycemic rats.